Iliocaval arteriovenous fistula following lumbar disc surgery - Duz, Bulent; Kaplan, Metin; Gunay, Celalettin; Ustunsoz, Bahri; Ugurel, Mehmet Sahin (Turkish Neurosurgical Soc, 2008)
Arteriovenous (AV) fistulae, pseudoaneurysms, and lacerations may occur during disc surgery. AV fistula after lumbar disc surgery is rare. Early diagnosis and treatment of vascular complications associated with disc surgery is essential due to their high mortality and morbidity rates. We report a case report who was, presented with fistulous shunt between right common iliac artery and inferior vena cava fifteen days after operation for herniated discs at L4-L5 and L5-S1 levels. Treatment was transcatheter covered stent placement at the fistulous site of right common iliac artery using a self expandable stent-graft. We suggest use of minimally invasive interventional techniques in the management of suitable vascular injuries following lumbar disc surgery.
Keywords: anteriovenous fistulae; vascular complication; lumbar disc surgery; endovascular; stent graft